Wellbeing, symptoms of trauma, and personal resources in Palestinian professional helpers: a cross-sectional quantitative survey. (July 2021) - Pepe, Alessandro; Cavazzoni, Federica; Addimando, Loredana; Jaradah, Alaa; Obaid, Hania; Veronese, Guido
Abstract: Background: Professional helpers working in adverse circumstances are at risk of developing psychosocial stress and signs of primary and secondary trauma (eg, anxiety and hyperarousal). We used modelling to investigate whether and to what extent personal resources (ie, post-traumatic growth, sense of coherence, and wellbeing) of Palestinian helpers affected their experience of psychological distress and trauma symptoms. Methods: Eligible participants were professional health-care providers working in Gaza and the West Bank, occupied Palestinian territory, between June and October, 2018. We used the following quantitative measures: WHO Well Being Index (WHO-5), General Health Questionnaire (GHQ-12), Impact of Event Scale (IES-13), Sense of Coherence Scale (SOC-3), and Post-traumatic Growth Index (PTGI-10). Data were analysed by multivariate structural equation modelling with latent and empirical indicators to test the fit of these constructs to the empirical data. The model was specified to evaluate whether and to what extent mental resources may be interpreted as a set of protective factors mitigating risk factors. The study was approved by the ethics board of the University of Milano-Bicocca, Milan, Italy. Written consent was obtained from participants. Findings: 181 participants were enrolled, ranging in age from 18 to 65 years (mean 31·1, SD 8·7). 135 (75%) were men. The mean GHQ-12 score was 17·7 (SD 7·5), revealing a medium to high degree of psychological trauma. 60 (33%) participants reported low mood (although not necessarily depression) on WHO-5. The structural model showed an excellent fit (χ 2 [24] 31·8, p=0·132, root mean square error of approximation 0·043, 90% CI 0·019–0·077). Stronger personal resources were associated with lower levels of both psychological distress (β=–0·25, p<0·01) and trauma (β=–0·16, p<0·01). Personal resources were especially associated with reduced levels of anxiety (β=–0·23, p<0·01) and intrusion symptoms (β=–0·22, p<0·01). Interpretation: Our integrated model showed that, despite heavy psychological burden, perceptions of post-traumatic growth, coherence, and wellbeing are associated with reduced psychological distress. Targeted training of health-care providers focused on self-awareness of their personal skills and survival resources could improve their psychological health. The study was limited by the cross-sectional research design, and the outcomes of the structural model should be read in terms of probabilistic associations rather than cause-effect relationships. A second limitation concerns the kind of data collected. All the research instruments yielded self-reported quantitative scores, meaning that the standardised β weights in the model could potentially be an artifact of common method variance (ie, attributable to the measurement method rather than to the constructs themselves. Funding: None.